Influence of Spiritual Coping and Social Support on the Mental Health and Quality of Life of the Saudi Informal Caregivers of Patients with Stroke - Alquwez, Nahed (Journal of religion and health, 2021)
The research explored the influence of spiritual coping and social support on mental health and quality of life (QOL) of informal caregivers of stroke survivors in Saudi Arabia. The respondents were frequently using religious coping strategies than existential coping strategies. The respondents received higher support from significant others and lowest support from friends. The majority of the respondents had mild to moderate depression, while more than one-third had mild to severe anxiety. Psychological health received the highest QOL, while physical health received the poorest QOL. Spiritual coping and social support significantly influenced the informal caregivers’ mental health and QOL.